Enhanced endoxylanase production by Myceliophthora thermophila using rice straw and its synergism with phytase in improving nutrition. (July 2020) - Dahiya, Seema; Kumar, Anil; Singh, Bijender
Graphical abstract: Highlights: Endoxylanase production by Myceliophthora thermophila was enhanced 1.5-fold after optimization using rice straw. Endoxylanase improved the nutritional properties of wheat and rice flours. Synergistic action of phytase and endoxylanase further enhanced the nutritional properties of wheat and rice flours. Abstract: The goal of the present investigation was to attain the enhanced production of endoxylanase in submerged fermentation using different approaches followed by its utility in improving nutrition of wheat and rice flours along with phytase. Myceliophthora thermophila BJTLRMDU3 produced 51.70 U/mL of xylanase using rice straw as a substrate after optimization with 'one variable at a time' approach. After Plackett-Burman design study, sodium nitrate, K2 HPO4 and Tween 20 were selected as critical factors and further optimized by response surface methodology. Increased xylanase production (80.15 U/mL) was attained with 2.5 % (w/v) sodium nitrate, 1.25 % (w/v) K2 HPO4, and 2 % (v/v) Tween 20 at 40 °C. An overall 1.5-fold increase in xylanase production was achieved after statistical optimization. Applicability of M. thermophila xylanase (200 U/g flour) alone and in combination with phytase (15 U/g flour) from Aspergillus oryzae SBS50 in wheat and rice flours showed enhancement in nutritional qualities of both flours. About 45.67 %, 29.73 %, and 107.91 % increase in reducing sugars, soluble proteins and inorganic phosphate, respectively in wheat flour, while 94.16 %, 134.52 %, and 473.33 % increase in reducing sugars, soluble proteins and inorganic phosphate, respectively in rice flour was achieved at 60 °C and pH 5.0 by synergistic action of xylanase and phytase as compared to control having only xylanase.